Teaching English Literature Based on Minahasa Local Wisdom through the Magiyan Folktale - Merlin Maya Maukar (Austronesian: Journal of Language Science & Literature, 2026)
This research is motivated by the importance of teaching English literature that is not only oriented towards Western texts, but also able to integrate local wisdom as a learning resource relevant to students’ cultural identity. The Magiyan folktale from Minahasa is seen as having pedagogical potential because it contains narrative structures, cultural symbols, moral conflicts, and local values ​​such as obedience, forgiveness, divine justice, and cultural identity. The purpose of this study is to describe lecturers’ and students’ interpretations of the Magiyan folktale as a teaching material for English literature, identify the values ​​of local wisdom that emerge in the learning process, and formulate pedagogical strategies to recontextualize these values ​​to suit the needs of contemporary students. This study uses a qualitative approach with a descriptive-interpretive case study design. Data were obtained through semi-structured interviews with three lecturers and fifteen students, and supported by learning documents. Data were analyzed using reflective thematic analysis with reference to Alan Dundes’ folklore theory, Vladimir Propp’s folktale morphology, and culturally responsive pedagogy. The results show that Magiyan can increase student engagement, strengthen cultural identity awareness, and foster critical interpretation skills in English. However, learning requires support in the form of cultural context, a bilingual glossary, visual media, thematic discussions, and narrative structure mapping. In conclusion, Magiyan can be used as a local wisdom-based English literature teaching material that not only supports language competence but also develops students’ cultural literacy, ethical reflection, and critical thinking skills.